Слаботочный разряд в лазере на парах меди; Известия вузов. Физика; Т. 58, № 9 - Евтушенко Г. С. Геннадий Сергеевич; Федоров В. Ф. Валерий Федорович; Шиянов Д. В. Дмитрий Валерьевич; Федоров К. В. Кирилл Валерьевич; Торгаев С. Н. Станислав Николаевич; Кулагин А. Е. Антон Евгеньевич (2015, 2015)
Заглавие с экрана